The efficiency of nations in the struggle against the COVID-19 pandemic - Aktas, Emel; Ülengin, Füsun; Topcu, Ilker; Gundes, Eda Helin (IGI Global, 2022)
The COVID-19 crisis has caused unprecedented suffering across the world. Millions have become infected, and hundreds of thousands have lost their lives. Nations mobilised their health workers and infrastructure to curb the spread of the disease and cure the infected. This paper aims to investigate the efficiency of nations in their struggle against the COVID-19 and how their efficiency changed over time analysing data from June and December 2020 with a novel three-stage methodology. In the first stage, we clustered 107 nations into highly competitive, competitive, and non-competitive countries using their Global Competitiveness Index scores published by the World Economic Forum evaluate a country in a group of comparable countries. In the second stage, we used Data Envelopment Analysis to assess the efficiency of each nation. In the third stage, we investigated the relationship between countries' efficiency and performance in 66 variables published in the United Nations Human Development Report along with the long-debated aspect of a nation's political governance regime using Tobit regression. Based on the data in June and December, the USA and the UK were the worst performers in the highly competitive nations cluster, Chile and Peru were the worst performers in the competitive nations cluster, and Brazil and Mozambique were the worst performers in the non-competitive nations cluster, respectively. Air pollution, international inbound tourists, urban population significantly reduced while domestic credit and gross national income per capita significantly increased efficiency, but the political regime did not affect efficiency.
Keywords: Competitiveness Index; COVID-19; Human Development; Cluster Analysis; Data Envelopment Analysis; Tobit Regression